2019
DOI: 10.1080/07481187.2019.1688430
|View full text |Cite
|
Sign up to set email alerts
|

Men’s grief and support following pregnancy loss: A qualitative investigation of service providers’ perspectives

Abstract: Month EmbargoHow can I share it? As a Taylor & Francis author, you can post your Accepted Manuscript (AM) on your personal website at any point after publication of your article (this includes posting to Facebook, Google groups, and LinkedIn, plus linking from Twitter).Embargoes apply if you are posting the AM to an institutional or subject repository, or to a scholarly collaboration network such as Mendeley. (You can find embargo and other information for all our journals by searching in the open access cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Further, our review highlighted that men's needs also need to be considered by health professionals while attending hospital with their partners as they can often feel excluded [36,45]. These findings are in line with other systematic reviews conducted on the experience of parents' hospital journeys [12,57]. Four of the six interventions included in the review have shown that providing emotional support following miscarriage can contribute to the reduction of psychological morbidities in both men and women [23,37,39,40].…”
Section: Discussionsupporting
confidence: 80%
“…Further, our review highlighted that men's needs also need to be considered by health professionals while attending hospital with their partners as they can often feel excluded [36,45]. These findings are in line with other systematic reviews conducted on the experience of parents' hospital journeys [12,57]. Four of the six interventions included in the review have shown that providing emotional support following miscarriage can contribute to the reduction of psychological morbidities in both men and women [23,37,39,40].…”
Section: Discussionsupporting
confidence: 80%
“…Health professionals and the community ignore and disallow the father´s grieving for PD although it has been shown that PD does have repercussions for fathers [46]. It is necessary to determine the needs of fathers [51,52] and clearly recognize their grief [38,39,47,53]. Although the sample of fathers in this study as more limited than that of mothers, our study investigates the experiences and perceptions of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, emotional care should take differences in the resolution of grief between mothers and fathers into consideration, as it is concluded by the majority of studies included in this review. Congruent with Obst and Due (2019), it would seem that men’s grief experiences are very diverse, and existing grief measures may not catalog all the challenges and complexities of grief for men such as a lack of social acknowledgment for their grief and resulting needs or the expectations to support female partners. Illustrating the consequences of these differences in the grieving process, Tseng et al (2014) found that some mothers described a deep feeling of loneliness caused by the silence of their partners who avoided talking about the issue, resulting in an indescribable distance in the relationship and a sense of failure in their role as a woman, mother, and daughter.…”
Section: Discussionmentioning
confidence: 99%